The effect of particle size on dissolution rate of fast dissolving oral film containing diclofenac sodium - Fitrianti Darusman; Nyayu Ista Yulita; Gita Cahya Eka Darma (Pharmaciana, 2020)
Diclofenac sodium is a Non-Steroidal Anti Inflammatory Drugs that if being taken orally have the side effects of peptic ulcers and undergone the first pass metabolism, and also included in the Biopharmaceutics Classification System class 2 which resulted in the low rate of dissolution. This study aims to determine the influence of particle size reduction on the dissolution rate of diclofenac sodium in the form of an FDOF dosage. The formation of diclofenac sodium nanoparticles is carried out by ionic gelation method using chitosan and sodium tripolyphosphate as a crosslinker in various ratios characterized by Particle Size Analyzer and Scanning Electron Microscopy, then it is incorporated into the form of an FDOF that were prepared by solvent casting method at a dose of 12.5 mg using variations concentration of SSG as superdisintegrant and PEG 400 as plasticizer. From the research results, diclofenac sodium nanoparticles are formed in the ratio of chitosan-sodium tripolyphosphate 6:1, have a size of 804 nm and spherical-shaped. The best FDOF dosage formula is F8 containing HPMC E5 LV 35% as the film forming agent, SSG 8% as superdisintegrant and PEG 400 10% as plasticizer.Â  FDOF formula containing diclofenac sodium nanoparticles has a slightly bitter taste, disintegration time less than one minute, surface pH around 7 (neutral), drug content that meets the requirements of the range of determination which is 93.24 Â± 0.96, the cumulative amount of drug dissolved in the 28th minute is higher by 88.45% compared to FDOF containing diclofenac sodium raw material, which is only 70.0%.